2022
DOI: 10.1111/aec.13143
|View full text |Cite
|
Sign up to set email alerts
|

The diet of a specialist nectarivore in Australia: The little red flying‐fox (Pteropus scapulatus, Pteropodidae)

Abstract: The little red flying-fox (Pteropus scapulatus, Pteropodidae) is the most widely distributed of the four Australian mainland flying-fox (Pteropus) species. They move very large distances following foraging resources and congregate in large numbers which often causes human-animal conflict. To better understand the resources that drive these movements and aggregations, we investigated the diet of the little red flying-fox using data from five sources: (i) faecal eDNA metabarcoding of field sampled little red fly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…We obtained winter diet species lists from studies that observed black flying foxes winter feeding (Palmer 1997 ; Vardon et al 2001 ; Markus and Hall 2004 ; Griffith 2020 ), the results of fecal analysis in winter months (Bell et al 2021 ; Bradford et al 2022 ), and known winter flowering diet species for grey-headed flying foxes in areas sympatric with black flying foxes (Eby and Law 2008 ; Eby et al 2019 ). We compiled a major diet list and a possible diet list from these studies, to account for the species’ extensive geographic range and our uncertainty about their diet across Queensland.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We obtained winter diet species lists from studies that observed black flying foxes winter feeding (Palmer 1997 ; Vardon et al 2001 ; Markus and Hall 2004 ; Griffith 2020 ), the results of fecal analysis in winter months (Bell et al 2021 ; Bradford et al 2022 ), and known winter flowering diet species for grey-headed flying foxes in areas sympatric with black flying foxes (Eby and Law 2008 ; Eby et al 2019 ). We compiled a major diet list and a possible diet list from these studies, to account for the species’ extensive geographic range and our uncertainty about their diet across Queensland.…”
Section: Methodsmentioning
confidence: 99%
“…Becker et al 2022 similarly showed pulses of Hendra virus shedding were most intense after food shortages in the previous spring and in areas where black flying foxes were newly overwintering. Flying foxes are typically nomadic, nocturnal nectarivores that commonly forage on small fruits, nectar, and pollen from members of the Proteaceae and Myrtaceae families, notably Eucalyptus, Melaleuca, Banksia, and Corymbia species (Eby 1991 ; Bell et al 2021 ; Bradford et al 2022 ). The climatic conditions that prompt eucalypt (tribe Eucalypteae within Myrtaceae) reproduction vary by location, soil type, and season (Law et al 2000 ; Eby and Law 2008 ), creating a patchwork of resources across the landscape.…”
Section: Introductionmentioning
confidence: 99%
“…There are four species of pteropid bats or flying foxes in eastern and northern Australia: the little red flying-fox (Pteropus scapulatus), the spectacled flying-fox (P. conspicillatus), the black flying-fox (P. alecto) and the grey-headed flying-fox (P. poliocephalus) [89]. Little red flyingfoxes have the widest geographic distribution in Australia, ranging from Victoria in the south to tropical northern Queensland and west to Shark Bay in Western Australia [90]. They, and other flying fox species, are becoming increasingly urbanized with most roosts in human modified landscapes [91,92].…”
Section: Probable Vertebrate Hosts Of Jev In Australiamentioning
confidence: 99%